2023
DOI: 10.1177/20594364231181745
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis of tweets and government translations: Assessing China’s post-COVID-19 landscape for signs of withering or booming

Abstract: This article aims to gain insights into the prevailing public sentiment during the policy relaxation period by examining whether the post-COVID-19 landscape reflects signs of withering or booming conditions. Employing methods from natural language processing (NLP) and machine learning (ML), the analysis reveals a predominance of positive sentiment from December 7, 2022 to May 17, 2023, indicative of an optimistic perspective and a potentially flourishing environment. A predictive model based on logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Moreover, it applies to air traffic control, rapid response medical teams, finance, data analytics, forensic science, archeological research, competitive sports, and musical performance. Each field demands precision and real-time assimilation of vast information, facilitating the development of nuanced skills aligned with real-world applications (Lowell & Moore, 2020;Wang & Wang, 2023). This approach aligns with the industry's goal of producing interpreters' adept at handling the challenges inherent in different interpreting scenarios.…”
Section: Expertise Differences In Interpreting Accuracymentioning
confidence: 95%
“…Moreover, it applies to air traffic control, rapid response medical teams, finance, data analytics, forensic science, archeological research, competitive sports, and musical performance. Each field demands precision and real-time assimilation of vast information, facilitating the development of nuanced skills aligned with real-world applications (Lowell & Moore, 2020;Wang & Wang, 2023). This approach aligns with the industry's goal of producing interpreters' adept at handling the challenges inherent in different interpreting scenarios.…”
Section: Expertise Differences In Interpreting Accuracymentioning
confidence: 95%
“…This study contributes by evaluating the performance of these algorithms in comparison to traditional frequency-based text representation (TF-IDF) and prediction-based text representation (W2V) Experimental analysis was conducted on datasets including IMDB, Yelp, and tweets that were collected and labeled by researchers based on their sentiments. The results indicated that the model created using W2V and ANN demonstrated superior performance compared to other approaches (1)(2)(3)(4)19) .…”
Section: Classification Algorithmsmentioning
confidence: 96%
“…Sentiment analysis algorithms empower researchers to assess the emotional tone and sentiment conveyed within religious texts (Wang and Wang 2023). By automatically classifying text segments as positive, negative, or neutral, sentiment analysis sheds light on the affective dimensions of religious texts (Yusof et al 2015).…”
mentioning
confidence: 99%